2022
DOI: 10.1021/acsmedchemlett.2c00429
|View full text |Cite
|
Sign up to set email alerts
|

Fragment-Sized Thiazoles in Fragment-Based Drug Discovery Campaigns: Friend or Foe?

Abstract: Thiazoles exhibit a wide range of biological activities and therefore represent useful and attractive building blocks. To evaluate their usefulness and pinpoint their liabilities in fragment screening campaigns, we assembled a focused library of 49 fragment-sized thiazoles and thiadiazoles with various substituents, namely amines, bromides, carboxylic acids, and nitriles. The library was profiled in a cascade of biochemical inhibition assays, redox activity, thiol reactivity, and stability assays. Our study in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 36 publications
(65 reference statements)
0
5
0
2
Order By: Relevance
“…None of the compounds were redox-active, and only 22 was unstable at pH above 8.0, as our high-throughput plate reader assay determined. 48,55 However, refinement of the stability assessment by using an HPLC-based method and extending the treatment to 24 h at a pH of 7.4 revealed that most binders, with the exception of Next, effects on the crucial CRBN neosubstrates were evaluated in cellular models (Figure S5). Table 3 In previous efforts (Scheme 3), linkers were attached via a reductive amination sequence.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…None of the compounds were redox-active, and only 22 was unstable at pH above 8.0, as our high-throughput plate reader assay determined. 48,55 However, refinement of the stability assessment by using an HPLC-based method and extending the treatment to 24 h at a pH of 7.4 revealed that most binders, with the exception of Next, effects on the crucial CRBN neosubstrates were evaluated in cellular models (Figure S5). Table 3 In previous efforts (Scheme 3), linkers were attached via a reductive amination sequence.…”
Section: Resultsmentioning
confidence: 99%
“…The aqueous stability of all compounds was determined spectrophotometrically by following the changes in the absorption spectra of the compounds, as described previously. 55 Briefly, the final mixture contained: 10 mM sodium phosphate, pH 7.0, 8.0, or 9.0, and 50 μM of the tested compound. The final concentration of was 5% (V/V).…”
Section: Carbamoyl]mentioning
confidence: 99%
“…We attribute the high SNE of an estimated 3200-fold for compound 24 to its 2-aminothiazole ring which is known for redox activity, which is essential to the photo-CIDNP mechanism. [36] The thiazole ring is also found in vitamin B1 (thiamine) which is a known radical scavenger. In particular, this finding indicates that ultrahigh SNE properties can be reached by exploring the chemical space.…”
Section: Methodsmentioning
confidence: 99%
“…Wir führen die hohe SNE von schätzungsweise 3200‐fach für Verbindung 24 auf ihren 2‐Aminothiazol‐Ring zurück, der für seine Redox‐Aktivität bekannt ist, die für den Photo‐CIDNP‐Mechanismus wesentlich ist [36] . Der Thiazolring kommt auch in Vitamin B1 (Thiamin) vor, das ein bekannter Radikalfänger ist.…”
Section: Figureunclassified
“…Wir führen die hohe SNE von schätzungsweise 3200-fach für Verbindung 24 auf ihren 2-Aminothiazol-Ring zurück, der für seine Redox-Aktivität bekannt ist, die für den Photo-CIDNP-Mechanismus wesentlich ist. [36] Der Thiazolring kommt auch in Vitamin B1 (Thiamin) vor, das ein bekannter Radikalfänger ist. Diese Erkenntnis deutet darauf hin, dass durch die Erforschung des chemischen Raums ultrahohe SNE-Eigenschaften erreicht werden können.…”
unclassified